2021
DOI: 10.1038/s41467-021-23560-8
|View full text |Cite
|
Sign up to set email alerts
|

A pig BodyMap transcriptome reveals diverse tissue physiologies and evolutionary dynamics of transcription

Abstract: A comprehensive transcriptomic survey of pigs can provide a mechanistic understanding of tissue specialization processes underlying economically valuable traits and accelerate their use as a biomedical model. Here we characterize four transcript types (lncRNAs, TUCPs, miRNAs, and circRNAs) and protein-coding genes in 31 adult pig tissues and two cell lines. We uncover the transcriptomic variability among 47 skeletal muscles, and six adipose depots linked to their different origins, metabolism, cell composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 106 publications
12
68
1
Order By: Relevance
“…More importantly, in line with our findings, Asgr1-deficient mice showed more severe liver injury and elevated hepatocyte death upon Streptococcus pneumoniae infection than did WT controls [ 37 ], supporting genetic susceptibility to liver injury in ASGR1 deficiency. Furthermore, reanalysis of data from our recent work [ 38 ] showed that, from a phylogenetic point of view, the liver exhibited a relatively lower evolutionary divergence in transcriptional output and resilience (with a shorter total branch length of expression-based trees [0.77]) than lung (0.88), adipose tissue (0.86), kidney (0.84) and spleen (0.79), and was comparable to heart (0.77) and higher than skeletal muscle [0.67]) among nine mammalian species ( S10A and S10B Fig ). Of the single-copy orthologous genes shared by nine mammalian species, ASGR1 and genes spatially close to ASGR1 exhibited relatively lower ΔAIC values and thus are relatively lower species-specific expression differences in the liver (variation in expression across species not due to evolutionary history, or expression changes after correcting the evolutionary nucleotide divergence between mammals) ( S11A and S11B Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, in line with our findings, Asgr1-deficient mice showed more severe liver injury and elevated hepatocyte death upon Streptococcus pneumoniae infection than did WT controls [ 37 ], supporting genetic susceptibility to liver injury in ASGR1 deficiency. Furthermore, reanalysis of data from our recent work [ 38 ] showed that, from a phylogenetic point of view, the liver exhibited a relatively lower evolutionary divergence in transcriptional output and resilience (with a shorter total branch length of expression-based trees [0.77]) than lung (0.88), adipose tissue (0.86), kidney (0.84) and spleen (0.79), and was comparable to heart (0.77) and higher than skeletal muscle [0.67]) among nine mammalian species ( S10A and S10B Fig ). Of the single-copy orthologous genes shared by nine mammalian species, ASGR1 and genes spatially close to ASGR1 exhibited relatively lower ΔAIC values and thus are relatively lower species-specific expression differences in the liver (variation in expression across species not due to evolutionary history, or expression changes after correcting the evolutionary nucleotide divergence between mammals) ( S11A and S11B Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…S3A), out of which a large fraction was also classified as testis enriched. The highly specific expression of the testis is due to the testis-specific Sertoli and germ cells and has previously been described in human [ 2 ], pig [ 15 , 32 ], macaque [ 33 ], and mouse [ 34 ]. In contrast, a large portion of the genes is classified as low tissue specificity and detected in all tissues ( n = 7699), and this set of genes is also interesting to study further.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies [ 10 13 , 17 ] have characterized the architecture of chromatin in porcine tissues and cell types. These studies mainly compared chromatin organization between species or during early development, and limited data on the differences in chromatin organization between pig breeds were presented.…”
Section: Discussionmentioning
confidence: 99%
“…We separately constructed four Hi-C libraries for wild boar ATs (two libraries for ULB and GOM, separately) and three libraries for Bama pig ATs (one library for ULB and two libraries for GOM) according to a previously described in situ Hi-C method with some modifications [ 2 ]. We also downloaded one corresponding Hi-C library for ULB in Bama pig, which was generated using the same experimental protocol, from our previous study [ 17 ]. Briefly, 1 g of adipose tissue was cross-linked in 4% freshly prepared formaldehyde (Sigma Aldrich, Louis, MO, USA) for 30 min at room temperature, followed by quenching with glycine (Amresco, Solon, OH, USA) at a final concentration of 0.25 mol/L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation